(untitled) (Scientific journal of the Fergana State University, 2024)
The state is considering information on issues of increasing the efficiency of the educational process when teaching social sciences and humanities in education. Theoretically analyzed how effective information technologies are in the formation and development of human professional skills. When teaching fanlap using the educational process, the issues of developing students’ cognitive activity for the development of future professional skills are presented.